2003
DOI: 10.1242/jcs.00830
|View full text |Cite
|
Sign up to set email alerts
|

Foxj1 is required for apical localization of ezrin in airway epithelial cells

Abstract: Establishment and maintenance of epithelial cell polarity depend on cytoskeletal organization and protein trafficking to polarized cortical membranes. ERM (ezrin, radixin, moesin) family members link polarized proteins with cytoskeletal actin. Although ERMs are often considered to be functionally similar, we found that, in airway epithelial cells, apical localization of ERMs depend on cell differentiation and is independently regulated. Moesin was present in the apical membrane of all undifferentiated epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 65 publications
(82 reference statements)
4
74
0
2
Order By: Relevance
“…These cells most probably represented the ciliated cell type of the ductuli efferentes. Apical ezrin expression had previously been observed in ciliated airway epithelial cells (Huang et al 2003). In the male genital tract, however, different from the airway epithelium, ezrin appeared to be present also in the nonciliated cells (compare also Höfer & Drenckhahn 1996).…”
Section: Association Of He6/gpr64 With the Apical F-actin-ezrin Scaffoldmentioning
confidence: 61%
See 2 more Smart Citations
“…These cells most probably represented the ciliated cell type of the ductuli efferentes. Apical ezrin expression had previously been observed in ciliated airway epithelial cells (Huang et al 2003). In the male genital tract, however, different from the airway epithelium, ezrin appeared to be present also in the nonciliated cells (compare also Höfer & Drenckhahn 1996).…”
Section: Association Of He6/gpr64 With the Apical F-actin-ezrin Scaffoldmentioning
confidence: 61%
“…An apical area immediately below the ciliated tufts was positive for F-actin and ezrin, but was completely devoid of HE6/GPR64. Indeed, ezrin has been found in the apical domain of specialized ciliated cells of the airway epithelium (Huang et al 2003) and may thus also be expressed in the ciliated cell type of the ductuli efferentes. A profilin-like protein that was previously suggested to link HE6/GPR64 to the actin cytoskeleton (Kirchhoff et al 2006), however, could not be verified by co-localization studies (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has recently been suggested that scaffolding proteins of the ezrin-radixin-moesin (ERM) family must be correctly localized at the PM for proper CFTR trafficking and function (Short et al, 1998;Mohler et al, 1999;Huang et al, 2003). Epithelial inflammation and remodeling have been reported to alter ERM protein expression (Laoukili et al, 2001), which could impair localization of ⌬F508 protein to the apical PM.…”
Section: Introductionmentioning
confidence: 99%
“…We used primary epithelial layers differentiated from murine (mouse) tracheal epithelia on permeable supports in culture as previously described. 17 The support is the plastic "insert" of the Ussing chamber (EC8225 Warner Instruments, Inc.) and is shown in panel a of Fig. 1.…”
mentioning
confidence: 99%